Effect of Workload and Career Development on Turnover Intention through Job Satisfaction as Variable Mediator - Jayasri, Roch Indah Agung; Annisa, Intan Tri (SAN Scientific, 2023)
This study aims to determine the effect of Workload and Career Development on Turnover Intention through Job Satisfaction as a Variable Mediator. The population used in this study were employees of PT Taiyo Sinar Raya Teknik with a total sample of 84 respondents. The sampling technique used was non-probability sampling with a purposive sampling technique using questionnaires distributed to respondents. Data analysis was carried out using SmartPLS 3. This study shows that workload has a positive and significant effect on turnover intention, career development has a negative and significant effect on turnover intention, job satisfaction has a negative and significant effect on turnover intention, workload has a negative and significant effect on job satisfaction, career development has a positive and significant effect on job satisfaction, job satisfaction can mediate workload on turnover intention, and job satisfaction can mediate career development on turnover intention